THE EVALUATION OF NATIONAL EXAMINATION OF ENGLISH SUBJECT AT SECONDARY SCHOOL - Indra Yoga Prawiro (Wiralodra English Journal, 2018)
The implementation of National Examination in Indonesia always becomes an interesting discussion both in education field and social life. One of the debates in the implementation of National Examination is about the fairness, many experts stated that the implementation of National Examination is unfair because the threeday exam is used to determine the success or failure of a student’s three years of high school. The second issue is about the quality of education in Indonesia’s school is gravely uneven. Some schools have luxury facilities and infrastructure, while others barely have a school building. So, to apply and expect the same standard from all of them is harsh and unrealistic. This study would like to analyze the questions in National Examination. The writer takes English test for science students as the primary data to answer the questions. The writer focuses on the principle of language assessment implemented in construction of English test in National Examination and the appropriateness of English test questions in National Examination based on the standardize of language assessment. The result shows that National examination in this case English test has been designed accordance to the principle of assessment. For standardized test of national examination, there are some types of test items are hardly to be found in the test. In terms of reading test items, multiple choices which are indicating to find reference words, phrase or sentence are not given in English test. It is dominated by finding out the detail or specific information about the text, implicit and general description about the text. Overall the English test in national examination has been design according to the standardized test. Only for several things need to be improved in term of test items variety in reading skill.